1984
DOI: 10.1021/j150655a029
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative technique for the determination of the number of unoccupied d-electron states in a platinum catalyst using the L2,3 x-ray absorption edge spectra

Abstract: This paper describes a new technique to quantitatively extract the number of unoccupied d states in a material utilizing measurements of the L X-ray absorption edge spectra. A correlation between the area under each of the L2 and L3 X-ray absorption edges and d-band vacancies in platinum-containing materials which exhibit white lines is given for the first time. The technique is demonstrated with a platinum catalyst supported on silica as an example. The quantity determined is the fractional change of the d-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
290
1
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(301 citation statements)
references
References 3 publications
5
290
1
5
Order By: Relevance
“…Since the white line (the large peak at the absorption edge) is assigned to the electron transition from 2p to 5d mainly, larger intensity of white line indic,4tes larger vacancy in 5d orbital. Unoccupied d-electron density was calculated according to the manner described by Mansour et al (1984a) from the comparison of the area intensities in the range from -10 to 25 eV in L m and lqt-edge XANES of catalysts with those of Pt foil assuming that unoccupied d-electron density per Pt atom for metallic platinum is 0.30 (Mansour et al, 1984b). A tendency could be observed that the platinum on the stronger acid support has the larger unoccupied d electron density, except for the silica-supported catalyst, or, in other words, acidic support, which is electrophilic, • BET surface area measured through N 2 adsorption at 77K, ~ acid strength determined by Hammett indicator method, = dispersion measured through the pulseadsorption of CO in a flow of the He gas, ' the conversion of catalytic combustion of C~l-l, at 523 K measured in a flow reactor under the followed condition; C~Hs 0.25%, 02 3%, N2 balance; 200 ml/min, "JRC-MGO-1 (JRC: Japan Reference Catalyst), I purchased by Kishida chemicals, • prepared by calcination of Zr(OH)z, which was obtained by hydrolysis of ZrOCI.,8H=O, , JRC-ALO-4, ' JRC-SIO-8, J JRC-SAIr2 (Si02-A1203 mixed oxide with 13 wt% A1203), ~ obtained in the same manner as in the literature (Ishikawa et aL, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Since the white line (the large peak at the absorption edge) is assigned to the electron transition from 2p to 5d mainly, larger intensity of white line indic,4tes larger vacancy in 5d orbital. Unoccupied d-electron density was calculated according to the manner described by Mansour et al (1984a) from the comparison of the area intensities in the range from -10 to 25 eV in L m and lqt-edge XANES of catalysts with those of Pt foil assuming that unoccupied d-electron density per Pt atom for metallic platinum is 0.30 (Mansour et al, 1984b). A tendency could be observed that the platinum on the stronger acid support has the larger unoccupied d electron density, except for the silica-supported catalyst, or, in other words, acidic support, which is electrophilic, • BET surface area measured through N 2 adsorption at 77K, ~ acid strength determined by Hammett indicator method, = dispersion measured through the pulseadsorption of CO in a flow of the He gas, ' the conversion of catalytic combustion of C~l-l, at 523 K measured in a flow reactor under the followed condition; C~Hs 0.25%, 02 3%, N2 balance; 200 ml/min, "JRC-MGO-1 (JRC: Japan Reference Catalyst), I purchased by Kishida chemicals, • prepared by calcination of Zr(OH)z, which was obtained by hydrolysis of ZrOCI.,8H=O, , JRC-ALO-4, ' JRC-SIO-8, J JRC-SAIr2 (Si02-A1203 mixed oxide with 13 wt% A1203), ~ obtained in the same manner as in the literature (Ishikawa et aL, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…This value was determined by comparing the computed XANES spectrum of a clean Pt/Rh(111) surface with an experimental spectrum at a potential corresponding to the double-layer region, namely E = +0.4 V. More detailed information about the model structures and input parameters for the FEFF8 calculations are provided in the Supplementary Information. 4 , recorded in order of increasing potential with respect to the reversible hydrogen electrode (RHE). As the potential exceeds 1.0 V, significant changes occur: the absorption edge is shifted to higher energy, the whiteline increases in both width and peak intensity, and the absorption decreases in the post-edge region above 11573 eV.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…The L 3 edge white line (WL) intensity is directly related to the amount of unfilled d states. 31 Although the WL peak of the p-polarization at 0.45 V is a little broader than that of the Pt foil, the intensity of spolarization at 0.45 V is stronger than that of the reference . Additionally, the WL intensity of p-polarization was much lower than that of the spolarization.…”
mentioning
confidence: 94%